คุณภาพบริการและความพึงพอใจของผู้ใช้บริการใบแจ้งยอดบัญชีบัตรเครดิตทางอีเมล - ชีวะก้องเกียรติ, ญานิกา; ธีรวรรณวิวัฒน์, เดือนเพ็ญ (Journal of Applied Statistics and Information Technology, 2016)
E-Service has become a new approach of service delivery, mainly through the internet channel. The present study focused on one of its type - an eMail credit card statement service. The main purposes were to describe various aspects of perceived service quality and customer satisfaction and to examine the relationship between service quality dimensions and customer satisfaction in e-services. The study based on survey data collected from 400 customers (of a Bank) who resided in Bangkok and then using hierarchical multiple regression to analyze the data. Results showed that from the customers’ perspective, the eMail statement services were high in quality. Moreover, customers were highly satisfied with the e-services. There were positive relationships between all five dimensions of service quality and customer satisfaction. However, after controlling for demographic characteristics and credit card utilization behaviour, only the effects of the reliability and the responsiveness dimensions on customer satisfaction were statistically significant at 0.05 level.